Plan de marketing para la comercialización turística del hostal Carrizal Inn en el cantón Bolívar provincia de Manabí - Cobeña López, Danny Daniel (2014)
This research aims to develop a marketing plan for the Carrizal Inn hostel located in the city of Calceta. It was divided into three methodological phases being the following: situational analysis, market research and tourism marketing plan for Carrizal Inn hostel. In the first phase of the study area boundary starting from the coordinates of the site of the Hostel in relation to the major cities of Ecuador was made; an internal and external analysis using matrices as EFI EFE matrix competitors and FODA matrix was also performed; that allowed for a more technical study of the establishment. In the study of market supply and demand Hostel currently analyzed. To analyze the offer was made a table showing the services provided by the Hostel in its rates; in the study of occupational demand capacity where issues such as historical demand, future demand, demand and potential demand objective considered was made. The profile of the visitor coming to the Hostel was also determined. Logo and slogan, promotional brochure, and website promotion and social networks: an advertising plan which consists of three programs was developed. Marketing mix strategies were established to minimize gaps in the Hostel. Among the results established that the development of this marketing plan as the Hostel has a low occupational cup despite providing quality services and possess excellent infrastructure is feasible.